2021
DOI: 10.2147/rmhp.s316844
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Expenditures and Health Outcomes in Pakistan: Evidence from Quantile Autoregressive Distributed Lag Model

Abstract: Objective The provision of healthcare facilities remains high on the manifesto of various political parties in Pakistan and healthcare spending has witnessed a significant surge in the last two decades that is expected to positively influence health outcomes in the country. Therefore, this research aims to explore the effects of healthcare expenditures on the actual health status of the masses in Pakistan for the period 1995Q1 to 2017Q1. Methods We apply the Quantile Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Gupta [45] argued that public spending enhances health and education in developing and emerging economies. Ullah et al [46] findings confirm that public healthcare spending significantly impacts health outcomes in Pakistan both in the short-run and long-run. Using a fixed effect model, Nixon and Ulmann [19], in a panel of 15 European Union members over the period 1980-1995, showed that health care expenditure and infant mortality rates were strongly associated, while the results for life expectancy were found to be marginally associated.…”
Section: Literature Reviewmentioning
confidence: 81%
“…Gupta [45] argued that public spending enhances health and education in developing and emerging economies. Ullah et al [46] findings confirm that public healthcare spending significantly impacts health outcomes in Pakistan both in the short-run and long-run. Using a fixed effect model, Nixon and Ulmann [19], in a panel of 15 European Union members over the period 1980-1995, showed that health care expenditure and infant mortality rates were strongly associated, while the results for life expectancy were found to be marginally associated.…”
Section: Literature Reviewmentioning
confidence: 81%
“…33 Nevertheless, future line of research can also explore the influence of lack of infrastructure and funding for the welfare of healthcare workers in developing countries on their emotional well-being. [34][35][36]…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…This puts strain on a variety of urban amenities, including sanitation, and sewerage systems, which in turn contributes to the deterioration of the surrounding environment. In addition, as a result of the massive flood of people and the unplanned housing societies, there has been observed an increasing drift of deforestation, which has further contributed to the deterioration of the situation ( 90 ). There is also evidence for an inverse relationship between the CE and URB nexus in Nigeria's economy, according to Kaleem Khan et al ( 91 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the result that spending on health care in both the public and private sectors led to a reduction in the environmental pollution in Asia, This study also shows that the private health sector has a greater negative impact on CO 2 emissions than the public sector. This result is based on comparing the two sectors' expenditures on healthcare ( 90 ).…”
Section: Resultsmentioning
confidence: 99%